EPISTEMOLOGI TAFSIR SUFI AL-GHAZALI DAN PERGESERANNYA - Wahyudi Wahyudi (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2018)
Abstract: In the history of tafsir development, there is a certain moment where there are some interactions between the Qur'an and the Sufis. Epistemologically, Sufis have a peculiar characteristic in looking at the Qur'an. The Sufis thaught that the Qur'an has two dimensions, esoteric and exoteric. These two sides are one unity and can not be separated. Al-Ghazali has its own nomenclature to refer to the ẓahir and inner sides of the Qur'an. The esoteric and exoteric dimensions of the Qur'an in the term al-Ghazali are called ‘ilm sadf and ‘ilm lubāb. The process of crossing from sadf to lubāb involves the role of imagination in istiqāmah suluk ilā Allāh. Viewed from the perspective of epidemiological division ala Abid al-Jabiri, the epistemology of al-Ghazali include the category of 'irfānī. But in its development al-Ghazali made a dialectic between the epistemology 'irfānī and bayānī at the same time, although the nuances of irfānī still remain dominant. This research attempts to answer the problem of how the process of the dialectic epistemology of al-Ghazali and how its building style. This kind of dialectic is one of al-Ghazali effort to built the harmonization between sadf science which tends to bayānī with the science of lubāb which tend to irfānī. Clearly, the process of this dialectic can be seen in one of his works Ihyā’ 'Ulūm al-Dīn. This research uses the qualitative method and includes library research. Abstrak: Dalam sejarah perkembangan tafsir, ada momen tertentu saat terjadi interaksi antara al-Qur’an dan kaum Sufi. Secara epistemologis, para Sufi memiliki ciri khas dalam memandang al-Qur’an. Kaum Sufi memandang bahwa Qur'an memiliki dua dimensi, esoterik dan eksoteris. Dua dimensi ini merupakan satu kesatuan dan tidak dapat dipisahkan. Al-Ghazali memiliki nomenklatur tersendiri untuk menyebut sisi ẓahir dan baṭin al-Qur’an. Dimensi esoterik dan eksoterik al-Qur’an dalam istilah al-Ghazali disebut dengan ‘ilm sadf dan ‘ilm lubab. Proses penyebrangan dari sadf ke lubāb ini melibatkan peran khayal dengan cara istiqāmah suluk ilā Allah. Ditinjau dari perspektif pembagian epistemologi ala Abid al-Jabiri, epistemologi al-Ghazali masuk dalam kategori ‘irfānī. Namun dalam perkembangannya al-Ghazali melakukan dialektika antara epistemologi ‘irfānī dan bayānī secara bersamaan, meskipun nuansa ‘irfānī masih tetap dominan. Penelitian ini berupaya untuk menjawab rumusan masalah bagaimana proses dialektika epistemologi al-Ghazali dan bagaimana corak bangunannya. Dialektika ini merupakan upaya harmonisasi al-Ghazali antara ilmu sadf yang cenderung bayānī dengan ilmu lubab yang mendekati ‘irfānī. Secara jelas proses dialektika ini dapat dilihat dalam salah satu karyanya Ihyā’ Ulūm al-Dīn. Penelitian ini menggunakan metode kualitatif dan merupakan penelitian kepustakaan.